The Influence of Internationalization, Marketing Capabilities, and Export Assistance on Export Performance in the Roots and Tubers Sector of Costa Rica - Johanna Alejandra Aristizábal Galvis; Luis Vinicio Losilla Solano (Innovar: Revista de Ciencias Administrativas y Sociales)
The export performance of small and medium-sized enterprises (SMEs) is a driver of socio-economic development in developing countries. Despite the limitations they face in technology, performance, and human and financial resources, many of them seek opportunities in international markets. This study aims to fill the gap in understanding the drivers that promote export performance of SMEs in emerging economies by evaluating the influence of the level of internationalization, marketing capabilities, and export assistance on export performance. The internationalization process was analyzed from a strategic perspective using resource-based view (RBV) and network approaches. A descriptive and quantitative study was conducted using an online survey administered to roots and tubers (R & T) export companies in Costa Rica. The results demonstrated a significant positive influence of company size, managerial marketing, and market diversification on export performance. Additionally, a significant negative influence of the level of internationalization on export performance was found. The findings of this study have managerial and policy implications for export managers and policymakers to implement proactive strategies effectively that increase SMEs export performance in developing countries and reduce barriers to their international expansion. Further studies are required to obtain greater robustness of the proposed model and identify significant effects.